Psychopolitics: conversations with Trevor Cribben Merrill - Oughourlian, Jean-Michel (Studies in violence, mimesis, and culture, 2012)
Psychopolitics -- War and terrorism -- The war of the gods -- Mimetic rivalry on an international scale -- Politics and religion -- The apocalypse -- Is there any hope? -- In conclusion